Tiktok Utilization as Youth Contribution in Improving The Economy and Creating Jobs in the Era of Society 5.0 - Arya Kemuning; Wartoyo Wartoyo (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
Developments in technology and the internet have had a major impact on changes in business and e-commerce in Indonesia. One example is the TikTok application, apart from being used for entertainment, it contains various kinds of information regarding education, news, employment and can even be used as a business area. This research was conducted using qualitative research. The data that the author obtained comes from the Tik Tok application. The data source that the writer takes is the Tik Tok video, and the data that the writer chooses is a video related to selling product promotions. Testing the validity of the data in this study includes 4 stages, namely the internal validation stage of member checking data, external validation of compiling reports systematically, reliability and objectivity or confirming to informants. Based on the results of the research and discussion that the authors have done, the conclusions that can be drawn are: 1.) Utilizing the Tik Tok application as a form of contribution for young people can improve the economy and create jobs. So young people can take advantage of the Tik Tok application for various businesses including: 1. Making content more interesting and creative, 2. Branded hashtag challenges and 3. Brand promotions by utilizing influencers. The tik tok application can also create jobs such as: 1. Become an agent for a product, 2. Become a reseller and 3. Become a content creator for a product. 2. The Tik Tok application is very influential in the business world. Besides being used to accompany free time, the Tik Tok application is also very useful for promoting a product and can even be used as an application for creating creative content.